Rigid bronchoscopy for foreign body removal: an overview - K., Shashidhar; V. Rajan, Roshna Raj; Shah, Nizin; Bhat, Nikhil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Foreign body aspiration is a potentially life threatening medical scenario. Immediate diagnosis and intervention can save the many adverse outcomes. The aim of our study was to determine the pattern, presentation and management of foreign body aspiration in our population. Methods: This is a retrospective study carried out in the Department of ENT and Head and Neck Surgery And Surgical Oncology, Karnataka Institute of Medical Sciences, Hubballi comprising of 22 patients with foreign body aspiration admitted to our department from July 2015 to February 2017.All patients with high suspicion of foreign body aspiration were included in our study. All patients underwent rigid bronchoscopy under general anesthesia. Results: In our study, majority of our patients were in the paediatric age group below the age of three years. History was always accidental inhalation of the foreign body. Areca nut was the most common foreign body removed. All patients who underwent successful foreign body removal following rigid bronchoscopy completely recovered from their ailments. Conclusions: It could be concluded that rigid bronchoscopy is treatment of choice in management of foreign body aspiration especially in pediatric population. The gold standard for the diagnosis and management of this condition is rigid bronchoscopy under general anaesthesia.